SAFETY DOOR WITH COMPUTER -BASED PASSWORD - Denny Sulistyo; Ir. Irwan Nimara, MM (Jurnal Sistem Komputer, 2000)
The address indicates a location, for that addr ess is unique, so there is only one location with one address.Â  Address used on the PC processor to be able to communicate with each section as well as on the PC to be able to communicate or control the application work as a safety door.Â